2017
DOI: 10.4102/sajhivmed.v18i1.707
|View full text |Cite
|
Sign up to set email alerts
|

Patient and provider attitudes to emergency department-based HIV counselling and testing in South Africa

Abstract: BackgroundThe national South African HIV Counselling and Testing (HCT) guidelines mandate that voluntary counselling and testing (VCT) should be offered in all healthcare facilities. Emergency departments (EDs) are at the forefront of many healthcare facilities, yet VCT is not routinely implemented in this setting.MethodsWe conducted a cross-sectional study that surveyed patients and healthcare providers at a tertiary care ED in the spring and summer of 2016 to ascertain their attitudes to VCT in the ED. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Beliefs around confidentiality in our study are the single most significant modifiable attitude to improve HIV testing uptake. Our study findings are in line with other studies in sub-Saharan Africa and Europe, where the fear of a breach in confidentiality was found to be a major barrier to HIV testing, especially among the youth (7,(30)(31)(32).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Beliefs around confidentiality in our study are the single most significant modifiable attitude to improve HIV testing uptake. Our study findings are in line with other studies in sub-Saharan Africa and Europe, where the fear of a breach in confidentiality was found to be a major barrier to HIV testing, especially among the youth (7,(30)(31)(32).…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is the first study to use a validated instrument to examine the effects of demographics, the LO curriculum, knowledge, and attitudes on HIV testing acceptance in an emergency department setting in South Africa. Studies in South Africa have shown favorable patient responses to ED-based HIV testing (7) and the PICT process has been successful in normalizing the HIV testing process and increasing uptake (11,12). Figure 1…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Documenting an HIV diagnosis in this setting is not thought of as a priority. [ 31 , 40 , 41 ] Our study revealed a high rate of POC test acceptance across the SATS severity grades, indicating that critical illness was not a significant obstacle in practice to patients. Interestingly we also found that patients who reported a known diagnosis of HIV infection requested repeat testing in the ED.…”
Section: Discussionmentioning
confidence: 66%